Modification of forming stem and leaves of rise depending on the agro-ecological factors (Experimental biology, 2015)
Agri – environmebtal factors (nutrition area, dose, timing, fertilization methods) have a significant impact on the formation of a modification of the assimilation leaf surface udlineie intermodes on the main stem and lateral shoots.
Keywords: agri-environmental factors (nutrition area; dose; timing; fertilization metods); rise; modification of forming stem